mRNA-Based Vaccines Are Highly Immunogenic and Confer Protection in the Gnotobiotic Pig Model of Human Rotavirus Diarrhea - Hensley, Casey (2024)
Human rotavirus (HRV) is still a leading cause of severe dehydrating gastroenteritis globally, particularly in infants and children. Previously, we demonstrated the immunogenicity of mRNA-based HRV vaccine candidates expressing the viral spike protein VP8* in rodent models. In the present study, we assessed the immunogenicity and protective efficacy of two mRNA-based HRV trivalent vaccine candidates, encoding VP8* of the genotypes P[8], P[6], or P[4], in the gnotobiotic (Gn) pig model of Wa (G1P[8]) HRV infection and diarrhea. Vaccines either encoded VP8* alone fused to the universal T-cell epitope P2 (P2-VP8*) or expressed P2-VP8* as a fusion protein with lumazine synthase (LS-P2-VP8*) to allow the formation and secretion of protein particles that present VP8* on their surface. Gn pigs were randomly assigned into groups and immunized three times with either P2-VP8* (30 µg) or LS-P2-VP8* (30 µg or 12 µg). A trivalent alum-adjuvanted P2-VP8* protein vaccine or an LNP-formulated irrelevant mRNA vaccine served as the positive and negative control, respectively. Upon challenge with virulent Wa HRV, a significantly shortened duration and decreased severity of diarrhea and significant protection from virus shedding was induced by both mRNA vaccine candidates compared to the negative control. Both LS-P2-VP8* doses induced significantly higher VP8*-specific IgG antibody titers in the serum after immunizations than the negative as well as the protein control. The P[8] VP8*-specific IgG antibody-secreting cells in the ileum, spleen, and blood seven days post-challenge, as well as VP8*-specific IFN-γ-producing T-cell numbers increased in all three mRNA-vaccinated pig groups compared to the negative control. Overall, there was a clear tendency towards improved responses in LS-P2-VP8* compared to the P2-VP8*mRNA vaccine. The demonstrated strong humoral immune responses, priming for effector T cells, and the significant reduction of viral shedding and duration of diarrhea in Gn pigs provide a promising proof of concept and may provide guidance for the further development of mRNA-based rotavirus vaccines.